Preliminary study on dispersal, predation and germination of selected seeds by orangutans (pongo pygmaeus pygmaeus) - Pail, Tracy (Universiti Malaysia Sarawak (UNIMAS), 2013)
A study to determine the effectiveness and the ability of orangutans (Pongo pygmaeus pygmaeus) as an agent of seed dispersal was carried out in between January 2013 to February 2013 at Matang Wildlife Centre, Kuching Sarawak. A total of nine fruits from nine families were given. Approximately 2 kg of fruits were given to each adult while about 2 kg were given for three individuals of group juvenile at one time feeding per day. The retrieval seeds from fecal was collected and tested for germination. A total of three types of small-seeded plant species were germinated while two did not. Three broad range of fruit-processing behavior in orangutans such as swallowing, spitting and masticating was recorded. Orangutans act as an effective seed disperser towards some large-seeded and small-seeded trees. The maintenance of population of orangutan in wild is very important in regenerating and maintenance of tropical forest. The morphological of seeds are crucial aspects in determine the fate of seed deposited by orangutans